Combining Laser Resurfacing and Facial Rejuvenation Surgery - Hessler, Jill L.; Trujillo, Oscar (Facial Plastic Surgery, 2021)
Facial aging is a multifactorial process involving skin laxity, volume loss, facial rhytids and solar elastosis. Surgical interventions can address the laxity of the skin and restore volume loss but do not fully correct the texture of the skin. Historically, there were concerns over the safety of combining laser resurfacing with facelifting procedures, but now there is much evidence to support the safe use of this combination treatment. When done appropriately, the combination of laser resurfacing with facial rejuvenation surgery can provide a synergistic effect for optimal clinical results. Here, we review the many laser options available and how they may be combined safely with surgical facial rejuvenation. We also review clinical contexts and candidate selection to provide safe, reliable results and minimize complications.
Keywords: facelift; laser resurfacing; SMAS; facial rejuvenation